Import Quotas in the United States - Whittlesey, C. R. (Quarterly Journal of Economics, 1937)
Introduction, 37.— Establishment of import quotas in the United States, 39.— Administrative provisions, 44.— Size of quotas, 47.— Effects of import quotas, 51: (1) Quotas which were not filled, 52; (2) Tariff quotas which were filled, 54; (3) Absolute quotas which were filled, 54.— Conclusions, 62.